Determinan Belanja Daerah Kabupaten dan Kota di Provinsi Sumatera Selatan 2015-2019 - Cahya Wahyuningtyas, Cahya Wahyuningtyas; Tari Widati, Tari Widati; Dalili Batrisyia, Dalili Batrisyia; Saiful Anwar, Saiful Anwar (Jeksyah: Islamic Economics Journal, 2022)
This study aims to show the effect of Regional Original Income, Revenue Sharing Funds, and Total Population on Regional Expenditures for the Province of South Sumatra for the 2015-2016 period. The population of this study were eight districts/cities of South Sumatra. The quantitative analysis technique used in this research is panel data regression analysis. The technique of determining the sample uses the purpose sampling method. The results showed that partially and simultaneously local revenue had a positive and significant effect on regional spending. Furthermore, profit-sharing funds have a positive effect on regional spending. Meanwhile, the total population partially and simultaneously has a significant positive effect on regional spending. This research has implications, especially for the government of South Sumatra Province to improve the quality of the economy, human resources or natural resources to increase APBN revenues. The increase in income will increase the development of infrastructure and public facilities in the Province of South Sumatra.